Hypothyroidism Causing Pericardial Effusion: A Case Report - Mirwais, Sabawoon (Cureus, 2019)
Hypothyroidism is an endocrine disorder with worldwide prevalence that can affect multiple organ systems. It can be asymptomatic and subclinical or overtly symptomatic with a potential to get complicated by fatal pathologies. It is an established cause of pericardial effusion, which in turn can be complicated by cardiac tamponade and severe hemodynamic instability. Herein we report the case of a 68-year-old male with history of Graves’ disease treated with radioiodine ablation and consequent hypothyroidism, presenting with moderate pericardial effusion.